Genomic-based diagnosis of arrhythmia disease in a personalized medicine era. Issue 6 (1st November 2016) - Omar, Abdullah; Zhou, Mi; Berman, Adam; Sorrentino, Robert A.; Yar, Neela; Weintraub, Neal L.; Kim, Il-man; Lei, Wei; Tang, Yaoliang
ABSTRACT: Introduction : Although thousands of potentially disease-causing mutations have been identified in a handful of genes, the genetic heterogeneity has led to diagnostic confusions, stemming directly from the limitations in our arsenal of genetic tools. Areas covered : We discuss the genetic basis of cardiac ion channelopathies, the gaps in our knowledge and how Next-generation sequencing technology (NGS) and can be used to bridge them, and how induced pluripotent stem cell (iPSC) derived-cardiomyocytes can be used for drug discovery. Expert commentary : Univariate, arrhythmogenic arrhythmias can explain some congenital arrhythmias, however, it is far from a comprehensive understanding of the complexity of many arrhythmias. Mutational screening is a critical step in personalized medicine and is critical to the management of patients with arrhythmias. The success of personalized medicine requires a more efficient way to identify a high number of genetic variants potentially implicated in cardiac arrhythmogenic diseases than traditional sequencing methods (eg, Sanger sequencing). Next-generation sequencing technology provides us with unprecedented opportunities to achieve high-throughput, rapid, and cost-effective detection of congenital arrhythmias in patients. Moreover, in personalized medicine era, IPSC derived-cardiomyocytes can be used as 'cardiac arrhythmia in a dish' model for drug discovery, and help us improve management of arrhythmias in patients by developing patient-specific drug therapies with target specificity.